Plant Cell Wall as a Key Player During Resistant and Susceptible Plant-Virus Interactions - Kozieł, Edmund; Otulak-Kozieł, Katarzyna; Bujarski, Józef Julian (Frontiers in Microbiology, 2021)
Cell wall is a complex and integral part of plant cell. As structural element it sustains shape of the cell and mediates contact among internal and external factors. From some time we are aware about its involvement in both abiotic (like drought or frost) and biotic stresses (like bacteria or fungi). In contrast to bacterial and fungal pathogens, viruses are not mechanical destructors of host cell walls, but relatively little is known about remodeling of plant cell wall in response to viral biotic stress. New research results indicate that cell wall represents a crucial active component during plant response to different viral infections. Apparently, the cell wall genes and proteins do play key roles during interaction, having direct influence on the rebuilding of cell wall architecture. Plant cell wall is involved in both susceptibility as well as resistance reactions. In this review we summarize the important progress in the research on plant virus impact on cell wall remodeling. Analyses of essential defensive wall - associated proteins in susceptible and resistant responses demonstrate that the components of cell wall metabolism can affect the spread of the virus as well as activate the apoplast- and symplast-based defense mechanisms, thus contributing about the complex network of plant immune system. Although the cell wall reorganization during the plant-virus interaction is still a challenging task, the use of novel tools and methods to investigate its composition and structure will greatly contribute to our knowledge in the field.